Development of CFD simulation model of earth air heat exchanger for space cooling of a 36 M2 house in tropical climate Banda Aceh, Indonesia - Sarwo Edhy Sofyan; Khairil Khairil; Zhafran Maulana; Akram Tamlicha; Jalaluddin Jalaluddin; M. Syaukani (Politeknik Negeri Lhokseumawe, 2023)
The global warming makes the ambient temperature hotter and greater efforts are made to reach a comfortable temperature. The continuous use of air conditioners that consume electricity is also unsustainable for the surrounding environment. Several studies on thermal comfort have been conducted by various researchers. Earth-air heat exchangers (EAHE) with air-working fluids can be used as a passive contribution to reduce building energy requirements for heating or cooling purposes. It should be noted that there is very little information in the literature on the development of a CFD (Computational Fluid Dynamic) simulation model of an EAHE for space cooling of a 36 m2 house in a tropical climate, such as Banda Aceh, Indonesia. Therefore, this study aims to examine the performance of EAHE with several variations in design parameters, such as pipe length, pipe diameter, number of pipe bends, and the type of soil where the EAHE is installed, as well as the thermal regime of a 36 m2 house either with or without the use of EAHE. The simulation in this study was conducted with CFD ANSYS Fluent software. The inlet air temperature of EAHE was set to be the same as the ambient air temperature, namely 31.4oC. The simulation results reveal that for variations in pipe length, the highest drop in outlet air temperature was yielded by the 47 m pipe length, which is 26.8°C. In which an increase in pipe length causes a decrease in air outlet temperature. The variation in pipe diameter does not significantly affect the outlet air temperature. Where the average air temperature drop at the EAHE exit is 0.046oC. The variation in number of turns shows that the drop in outlet air temperature is identical, namely 28.2°C, despite the fact that their pressure drop values are different. In addition, it was found that the performance of EAHE buried under different types of soil is distinct. The highest drop in outlet air temperature was generated when the EAHE was buried in silty soil, namely 26.1°C. A case study on a 36 m2 house shows that the utilization an underground heat exchanger can reduce the house’s indoor temperature by 2°C, with an average house temperature of 30.4°C compared to that with a natural ventilation.